Freshwater turtle (Reptilia: Testudines) assemblage from an urban protected Atlantic Forest remnant: population density, movement and habitat preference - Sabine B. Rocha; Carlos Rouco; Carlos Eduardo V. Grou; Vanda Lúcia Ferreira (Zoologia (Curitiba))
ABSTRACT Urbanization may significantly impact wild population dynamics, even in protected green spaces. From 2016 to 2018, we accessed an assemblage of freshwater turtles isolated in an urban remnant of the Atlantic Forest, southern Brazil. We captured turtles by active search, hookless fishing, and funnel trap, and we marked them individually. Using a capture-mark-recapture method, we estimated population density, and movement, including home range size and habitat selection. Home ranges were estimated using the 100% minimum convex polygon method and habitat selections through eigenanalysis. We captured 41 specimens of Phrynops geoffroanus (Schweigger, 1812), 35 Trachemys dorbigni (Duméril & Bibron, 1835), and 20 Trachemys scripta elegans (Wied-Neuwied, 1839). The invasive T. dorbigni showed the highest density (1.72 individual/ha), followed by the native P. geoffroanus (1.36 individual/ha) and the invasive T. scripta elegans (0.87 individual/ha). Home range sizes for P. geoffroanus and T. dorbigni ranged between 0.04-0.48 ha, with the latter species covering the longest distance (525.8 m). All three species showed a preference for habitats influenced by human presence (walkways). Our findings highlight the anthropic influence on the movement of the freshwater turtle assemblage and underscore the need for enhanced protection of native species and control of invasive turtles. This study provides essential baseline data for future researches and management of urban areas.